Wire bonding in microelectronics materials, processes, realibility and yield - Harman, George G. (.Electronic packaging and interconnection series., 1997)
The wire bonding bible - now revised and expanded! Get the practical know-how you need to design and evaluate wire bonds engineered with the latest - and still-evolving- metallurgies. Extensively revised and updated, the Second Edition of George Harman's classic Wire Bonding in Microelectronics shows you step-by-step how to exploit new higherm density interconnection techniques and engineer reliable gonds at a very high yield. You get the hands-on guidance you need to test wire bonds...clean bond pads to improve bondability and realiability...solve cratering, heel cracks, bond fatigue, so-called purple plague and other mechanical problems....bond wires to multichip modules...and much, much more. You also get up-to-the-minute details on utilizing fine pitch SMT, applying new bonding metallurgies, and exploring wire sweep and the wire bonding mechanism.